2018
DOI: 10.1002/mc.22940
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of diabetes‐related genes, their interaction with diabetes status, and breast cancer incidence and mortality: The Long Island Breast Cancer Study Project

Abstract: To examine 143 diabetes risk single nucleotide polymorphisms (SNPs), identified from genome-wide association studies, in association with breast cancer (BC) incidence and subsequent mortality. A population-based sample of Caucasian women with first primary invasive BC (n = 817) and controls (n = 1021) were interviewed to assess diabetes status. Using the National Death Index, women with BC were followed for >18 years during which 340 deaths occurred (139 BC deaths). Genotyping was done using DNA extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A recent analysis where this has been attempted used 143 type 2 diabetes predisposing variants and investigated their association with risk of mortality in~800 people. Twelve SNPs were associated with risk of breast cancer, three with all-cause mortality and three with breast cancer specific mortality, yet none of the associations were significant after multiple testing corrections [104]. Until data from larger cohorts are available, power is likely to be an issue in such studies.…”
Section: Adipositymentioning
confidence: 99%
“…A recent analysis where this has been attempted used 143 type 2 diabetes predisposing variants and investigated their association with risk of mortality in~800 people. Twelve SNPs were associated with risk of breast cancer, three with all-cause mortality and three with breast cancer specific mortality, yet none of the associations were significant after multiple testing corrections [104]. Until data from larger cohorts are available, power is likely to be an issue in such studies.…”
Section: Adipositymentioning
confidence: 99%
“…The long island breast cancer study revealed that the genetic polymorphisms which account for an increased diabetes risk are involved in enhanced mortality and risk of developing breast cancer; for example, SLC30A8 (a zinc transporter insulin-related secretion gene), CDKN2A-CDKN2B (cell cycle related genes), IGFBP2 and IRS2 (Insulin pathway related genes). The single nucleotide polymorphisms (SNPs) listed indirectly suggest an association between genes involved in metabolic and molecular glucose signaling, the cell cycle, and risk/progression of cancer [38]. Type 2 diabetes (T2D) associated SNPs are also present in JAZF1 , which plays an important role in stromal cancer oncogenesis.…”
Section: Hyperglycemia and Risk Factors For Cancermentioning
confidence: 99%
“…HHEX was found to play a role in the migration and invasion of breast and prostate epithelial cells through the direct transcriptional regulation of Endoglin. The association of HHEX with hematopoietic, colorectal, liver, breast, prostate, and thyroid cancers has been extensively reported [31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%